(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines ways to address methodological issues in studying natural ecological and natural-technical systems with the goal of identifying the most effective methods for obtaining information that supports measures for the rational use of natural resources and environmental protection.